FROM THE LIFE HISTORY OF MUNAVVAR QORI ABDURASHIDKHANOV - Mahmudov is the son of Zoirbek Tahirjan (PEDAGOGS, 2024)
Abstract: Through this article, a lot of information about the life of one of our great grandfathers, Munavvar Qori Abdurashidkhanov, will be revealed. In the article, you can see Munavvar Kari's interest in studies, involvement in jadidism, creation of many jadid schools, textbooks, and his work in jadid activities.